1998
DOI: 10.1111/j.1469-7793.1998.083by.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of the phases of a Ca2+ spike by the store Ca2+‐ATPase in human umbilical vein endothelial cells

Abstract: Histamine‐stimulated cytosolic free Ca2+ ([Ca2+]i) oscillations in human umbilical vein endothelial cells (HUVECs) comprise repetitive spikes generated by pulsatile release from stores. We have investigated the roles of the store Ca2+‐ATPases in regulating both the upstroke and downstroke of a Ca2+ spike. The sarco‐endoplasmic reticulum Ca2+‐ATPase (SERCA) inhibitor cyclopiazonic acid (CPA) dramatically affected oscillations whereas inhibition of the plasma membrane Ca2+‐ATPase (PMCA) with La3+ had little effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
9
15
0
Order By: Relevance
“…Overall it appears that PMCA inhibition does not have a dramatic effect on oscillations in WT cells. This conclusion is consistent with previous reports of Morgan and Jacob (Morgan and Jacob, 1998) who found that inhibiting the PMCA with La 3+ (which could not be used in the present study because it is an agonist of CaR) had little effect on Ca 2+ oscillations in endothelial cells. Moreover, Green et al, also showed that another PMCA inhibitor, carboxyeosin (which also could not be used here due to its intense fluorescence) did not block Ca 2+ oscillations in rat hepatocytes as measured by the luminescent photoprotein aequorin (Green et al, 1997).…”
Section: Resultssupporting
confidence: 83%
“…Overall it appears that PMCA inhibition does not have a dramatic effect on oscillations in WT cells. This conclusion is consistent with previous reports of Morgan and Jacob (Morgan and Jacob, 1998) who found that inhibiting the PMCA with La 3+ (which could not be used in the present study because it is an agonist of CaR) had little effect on Ca 2+ oscillations in endothelial cells. Moreover, Green et al, also showed that another PMCA inhibitor, carboxyeosin (which also could not be used here due to its intense fluorescence) did not block Ca 2+ oscillations in rat hepatocytes as measured by the luminescent photoprotein aequorin (Green et al, 1997).…”
Section: Resultssupporting
confidence: 83%
“…However, the established routes for gated release of Ca 2+ may contribute to a physiological leak, since IP 3 R antagonists have been found to reduce Ca 2+ leakage from the ER after SERCA inhibition in intact cells [24][25][26]. In analogy to previous observations [60,61] …”
Section: Discussionmentioning
confidence: 53%
“…5). A large significant increase in the L p was measured with SKF, TG, and IM treatment, implying that the reason why there was no increase in L p with IM after CPA treatment was because CPA reduced the degree of Ca 2ϩ filling of the store, as expected (20). Once Ca 2ϩ influx was permitted the L p increased again.…”
Section: Does Store Emptying or Active Release Increase L P In Absencmentioning
confidence: 66%